Study of the echoes of the Arabic story in Nigerian Arabic literature: Ilorin as a case study - Abdur-Rasheed Mahmoud-Mukadam (Nady Al-Adab : Jurnal Bahasa Arab, 2019)
The story is an art of prose literature. Arab writers and others have done valuable works of fiction, showing the extent of their artistic ability; however, this art has witnessed in the modern era developed and developed to add to it another form known - in Western literature - poetry story; which has no era - before - in literature Old Arab, and the poems appeared stories woven on the Western vein. After looking at the story in Arabic literature, this article looks at some of the echoes of the Arab story in Arabic literature, with an emphasis on what the thinkers of the city of Eulen produced as a living model reflecting the many stories that were presented at the Arab literature table in Nigeria. For a commendable effort by the writers of Nigeria to expand the Arabic language and create a clear atmosphere for artistic creativity and conscience.